ANALISIS KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA PROGRAM STUDI TASAWUF DAN PSIKOTERAPI UNIVERSITAS MUHAMMADIYAH CIREBON - Abdul Basit Atamimi; Sri Maryati; Nissa Aulia Rakhmah (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
This study examines the psychological well-being of students at the end of the semester. Psychological well-being is an individual mental state that is positive and avoids stress, depression, and other mental disorders. Thus, this article aims to see how the picture of psychological well-being in the students of the final semester in particular in the Studies Program Sufism and Psychotherapy of the Faculty of Islamic Religion of Muhammadiyah University of Cirebon, with methods of qualitative research whose data is obtained through interviews and documentation studies. The results show that overall psychological well-being is divided into three categories. The first category is subjects who have good psychological welfare that meets the standard of the psychological wellness category that has six dimensions of psychological health. The third category is subjects with poor psychological well-being, which only meets two or three dimensions of psychological wellness.